Natural Ventilation in Building Buffer Spaces of Traditional Qiang Dwellings: Field Study in Western China - Ying Zhao; Kun Li; Meng Han; Jianwu Xiong; Yifan Zhang (Buildings)
As China’s rural revitalization progresses, the green and sustainable development of traditional dwellings has gained significant attention. Traditional Qiang dwellings in western Sichuan, located in high-altitude cold regions, often feature thick walls and small windows, limiting air circulation. Buffer spaces play a key role in improving indoor air quality and reducing energy consumption through natural ventilation. This study explores traditional Qiang dwellings in western Sichuan through field research, architectural analysis, and numerical simulations. The study analyzes three buffer space types and compares natural ventilation in dwellings with and without buffer spaces. The results show better air circulation in buildings with buffer spaces. The simulation further shows that when the courtyard’s aspect ratio is 1.3 and the width-to-height ratio is 0.9, ventilation and air renewal rates are optimized. Based on this, the study proposes natural ventilation optimization strategies to reduce reliance on mechanical systems and improve energy efficiency. The study provides a scientific basis for low-carbon Qiang dwelling design and offers practical strategies for improving living environments, supporting sustainable rural development.